(untitled) (Swiss Medical Weekly, 2020)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors are a new class of drugs that reduce blood glucose levels by increasing urinary glucose excretion. On top of the glucose-lowering effect, they offer cardiovascular and renal benefits, the mechanisms of which are probably pleiotropic and include blood pressure reduction, volume depletion, weight loss and several metabolic effects (such as lipolysis and synthesis of ketone bodies). SGLT2 inhibitors are currently indicated in Europe and the USA, as first- or second-line treatments of type 2 diabetes mellitus (T2DM) in patients with established cardiovascular disease, high/very high cardiovascular risk, renal disease or heart failure. The use of dapagliflozin has recently been extended to patients with heart failure without T2DM, as new emerging data show benefits in this population. Despite an overall favourable safety profile, attention has to be paid to the increased risk of euglycaemic diabetic ketoacidosis and genital mycotic infections, as well as lower limb amputations and fractures, which have been inconsistently associated with SGLT2 inhibition. For the moment, cost related data for the Swiss setting is lacking but corresponding analyses from abroad suggest cost-effectiveness. Despite their numerous favourable cardiorenal implications, many physicians remain hesitant to use SGLT2 inhibitors. In this article, we present an up-to-date narrative literature review of the physiological mechanisms of action, current indications, therapeutic utility and side effects of SGLT2 inhibitors.